Integrating climate change mitigation and adaptation in agriculture and forestry: opportunities and trade-offs - Locatelli, Bruno; Pavageau, C.; Pramova, E.; Gregorio, M. di (Wiley, 2015)
Although many activities can jointly contribute to the climate change strategies of adaptation and mitigation, climate policies have generally treated these strategies separately. In recent years, there has been a growing interest shown by practitioners in agriculture, forestry, and landscape management in the links between the two strategies. This review explores the opportunities and trade-offs when managing landscapes for both climate change mitigation and adaptation; different conceptualizations of the links between adaptation and mitigation are highlighted. Under a first conceptualization of ‘joint outcomes,’ several reviewed studies analyze how activities without climatic objectives deliver joint adaptation and mitigation outcomes. In a second conceptualization of ‘unintended side effects,’ the focus is on how activities aimed at only one climate objective—either adaptation or mitigation—can deliver outcomes for the other objective. A third conceptualization of ‘joint objectives’ highlights that associating both adaptation and mitigation objectives in a climate-related activity can influence its outcomes because of multiple possible interactions. The review reveals a diversity of reasons for mainstreaming adaptation and mitigation separately or jointly in landscape management. The three broad conceptualizations of the links between adaptation and mitigation suggest different implications for climate policy mainstreaming and integration.